Application of Computer Vision-Based Optoelectronic Target Tracking Algorithm in Command and Control System - Feng, Bo; Jia, Yanyan (2024 International Conference on Power, Electrical Engineering, Electronics and Control (PEEEC), 2024)
With the continuous improvement of modern war and security monitoring needs, the command and control system has more and more strict requirements on the precision and real-time of target tracking technology. The photoelectric target tracking algorithm based on computer vision has been widely used in command and control system because of its efficient and accurate features. In this paper, the basic principle of photoelectric target tracking algorithm and its application in command and control system are discussed in depth, focusing on analyzing the selection and realization methods of different algorithms and their effects in practical application. Through the comparative analysis of several typical algorithms, this paper reveals the potential of optoelectronic target tracking algorithms in enhancing the efficiency and accuracy of command and control systems, and points out the challenges faced by the current technology and the future development direction. The results show that with the development of emerging technologies and the continuous optimization of algorithms, optoelectronic target tracking will play an increasingly important role in command and control systems.